The Effect of Human Resources Competence, Internal Audit and Information Technology Utilization on the Quality of Financial Statements in Public Service Agency Hospitals - Endang Ruhiyat; Nurmala Ahmar; JMV. Mulyadi; Harnovinsah (Dinasti Publisher, 2025)
This study aims to examine the effect of human resource competence (HR), information technology utilization, and internal audit on the quality of financial statements in Public Service Agency Hospitals (BLU Hospitals). This study uses a quantitative approach with multiple linear regression analysis, involving financial statement data from 13 BLU hospitals located in Jakarta, Tangerang, and Bogor in 2022. Independent variables include HR competencies, information technology utilization, and internal audit, while control variables include age, length of service, education, and gender. The results showed that HR competence has a positive and significant effect on the quality of financial statements, especially in terms of timeliness of submission and reliability of the information presented. The use of information technology has a significant effect on the efficiency and accuracy of the financial reporting process, which supports increased transparency. Internal audit significantly affects the quality of financial statements by ensuring compliance with regulations, the effectiveness of the internal control system, and the minimization of material errors. Control variables, such as education and length of service, showed a moderate relationship to financial statement quality, but were not dominant compared to the main variables. This study makes a practical contribution by suggesting continuous training programs to improve HR competencies, adoption of more sophisticated financial information systems, and strengthening the internal audit function.